Perivascular adipose tissue promotes vascular dysfunction in murine lupus - Shi, Hong; Goo, Brandee; Kim, David; Kress, Taylor C.; Ogbi, Mourad; Mintz, James; Wu, Hanping; Belin de Chantemèle, Eric J.; Stepp, David; Long, Xiaochun; Guha, Avirup; Lee, Richard; et al. (Frontiers in Immunology, 2023)
Patients with systemic lupus erythematosus (SLE) are at elevated risk for cardiovascular disease (CVD) due to accelerated atherosclerosis. Compared to heathy control subjects, lupus patients have higher volumes and densities of thoracic aortic perivascular adipose tissue (PVAT), which independently associates with vascular calcification, a marker of subclinical atherosclerosis. However, the biological and functional role of PVAT in SLE has not been directly investigated. Using mouse models of lupus, we studied the phenotype and function of PVAT, and the mechanisms linking PVAT and vascular dysfunction in lupus disease. Lupus mice were hypermetabolic and exhibited partial lipodystrophy, with sparing of thoracic aortic PVAT. Using wire myography, we found that mice with active lupus exhibited impaired endothelium-dependent relaxation of thoracic aorta, which was further exacerbated in the presence of thoracic aortic PVAT. Interestingly, PVAT from lupus mice exhibited phenotypic switching, as evidenced by “whitening” and hypertrophy of perivascular adipocytes along with immune cell infiltration, in association with adventitial hyperplasia. In addition, expression of UCP1, a brown/beige adipose marker, was dramatically decreased, while CD45-positive leukocyte infiltration was increased, in PVAT from lupus mice. Furthermore, PVAT from lupus mice exhibited a marked decrease in adipogenic gene expression, concomitant with increased pro-inflammatory adipocytokine and leukocyte marker expression. Taken together, these results suggest that dysfunctional, inflamed PVAT may contribute to vascular disease in lupus.